Pengembangan Multimedia Interaktif Menggunakan Aplikasi Articulate Storyline pada Mata Pelajaran Informatika Kelas X SMA - Rahmi, Azizu; Yeni J, Fetri; Rahmi, Ulfia; Amilia, Winanda (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Learning in the classroom, teachers have not optimized the use of media other than LKS, so students tend to be bored because they do not understand the material because the images are not clear in the LKS. This research aims to produce interactive multimedia that is valid and practical so that it can be used by teachers, especially in informatics subjects. This type of research is Research and Development (R&D) research, the development model used is the 4-D (Define, Design, Development, & Disseminate) development model. The subject of the study is class X students of SMA Pertiwi 1 Padang with a total of 20 students. In the research process, data collection by observation and using questionnaires. Data processing obtained from media validation, material validation and student practicality tests with assessment using a Likert scale questionnaire with a score range of 1 to 5. Validity Test, validation from material experts with an average score of 4.87 in the very valid category, validation results from media experts obtained an overall average of 4.85 in the very valid category. The results of the practicality test on students obtained an average score of 4.62 with the category of very practical. Based on these results, interactive multimedia using the Articulate Storyline application in the informatics subject class X of high school is very valid and practical to be used as a learning medium